Analisis Prediksi Kebangkrutan Dengan Metode Altman Z-Score: (Studi Kasus PT. Gudang Garam Tbk) - Nadila Eka Pratiwi; Rhezka Arianti Daulay; Siti Nenti Indriani (J-CEKI : Jurnal Cendekia Ilmiah, 2022)
The purpose of this study was to determine the potential level of bankruptcy that occurred in the cigarette industry companies listed on the Stock Exchange, namely "PT. Gudang Garam Tbk” using the Altman z-score method. In various studies Altman Z-score (bankruptcy model) is used as a measurable control tool on the financial status of a company that is experiencing financial distress (financial distress).The results of the bankruptcy analysis using the Altman Z-Score method of PT Gudang Garam Tbk from 2016 to 2021, the company's financial condition is in a healthy condition meaning that it does not experience bankruptcy. Every year the results exceed the standard Z-Score which is 2.90. and there is no negative value of the ratio. This shows that the company's financial performance is good.